Perencanaan Produksi Makanan Laut dengan Pertimbangan Permintaan dan Kapasitas - Hirman Rachman; Herman Mawengkang (Journal of Mathematics: Theory and Applications, 2023)
The sea holds many resources that are very important for life, and one of them is the potential of fisheries, which is a basic human need. Indonesia, as a maritime country whose waters cover 2/3 of its territory, most of its people who live in coastal areas have utilized this condition by conducting fisheries management activities. However, the process still needs technical support to optimize the results. This research will review the production planning process of processed marine products under demand uncertainty. This research will construct a model to minimize production costs by considering demand uncertainty. The model will be computed using Mixed Integer Linear Program (MILP) method to provide the decision of processed products produced and the amount of production.